2002
DOI: 10.1081/iph-120016039
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Glutoxim on Some Activities of Isolated Human Neutrophils and in Whole Blood

Abstract: Activity of Glutoxim, a sulfur-containing hexapeptide with immunomodulating effect on lymphocytes, was studied on human neutrophils. Commercial available agent containing the substance, Glutoxim, was used. At the doses of 1, 3, 6 or 100 microg/mL the drug stimulated the superoxide anion and hypochlorous acid generation in resting neutrophils but inhibited them in cells stimulated with zymosan or PMA. The only inhibiting effect was observed on nitric oxide production in LPS-stimulated RAW 264.7 cells. The drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Glutoxim has a immunomodulating effect on lymphocytes showing chemoattractant activity on cells and inhibiting fMLP-induced chemotaxis. Fimiani et al, 2002 50 mg/kg Glutoxim increased the receptor-mediated expression of GR, GPx and GTS, increased the expression of HSP70 in the model of acute cerebral ischemia. systems for the regulation of many cellular processes.…”
Section: Belenichev Et Al 2020mentioning
confidence: 90%
See 1 more Smart Citation
“…Glutoxim has a immunomodulating effect on lymphocytes showing chemoattractant activity on cells and inhibiting fMLP-induced chemotaxis. Fimiani et al, 2002 50 mg/kg Glutoxim increased the receptor-mediated expression of GR, GPx and GTS, increased the expression of HSP70 in the model of acute cerebral ischemia. systems for the regulation of many cellular processes.…”
Section: Belenichev Et Al 2020mentioning
confidence: 90%
“…The positive effects of the drug on LP markers are described, glutoxim reduces the level of diene conjugates and malonaldehyde against the background of an increase in the antioxidant enzymes SOD and catalase ( Belenichev et al, 2020 ; Table 2 ). Today, the drug is successfully used in phthisiology, oncology, gastroenterology, gynecology, narcology, and toxicology, surgery ( Fimiani et al, 2002 ; Wasinger et al, 2018 ).…”
Section: Possible Pathways For Activation Of Hsp70-dependent Mechanis...mentioning
confidence: 99%
“…Adverse effects were limited to transient febrile events that resolved on discontinuation of the drug. Preclinical studies in human neutrophils and whole blood demonstrated an immunomodulatory mode of action [47], suggesting that immunomodulatory peptide-based drugs can be safe and effective. Glutoxim is currently undergoing phase III clinical trials in the USA as a chemotherapy adjuvant (http://www.clinicaltrials.gov/ct2/ show/NCT00347412) in non-small-cell lung cancer rather than as an anti-infective, possibly because of the relatively low incidence of tuberculosis in the USA and lesser potential for return on investment.…”
Section: Reviewmentioning
confidence: 99%
“…Several other immune response modifiers that target different stages of innate immunity and might be useful for plague therapy have recently been reviewed (Amlie- Lefond et al, 2005;Masihi, 2000), but only one, glutoxim, a sulfur-containing hexapeptide with an immunomodulatory effect on lymphocytes (Fimiani et al, 2002), has been used in an animal model of plague (Zhemchugov, 2004). When injected into mice (12?5 mg per animal) 6 h before challenge with 10 LD 50 of the virulent Y. pestis strain 231, it protected half of the animals from death.…”
Section: Antibiotic Prophylaxis and Therapymentioning
confidence: 99%